Analysis of Patient Rights Protection through Medical Record Confidentiality and Information Disclosure System in Indonesian Hospitals - Ns. I Komang Upadana Putra; Tuty Kuswardhani; Sagung Putri M.E Purwani (Borong Newinera Publisher, 2024)
This study presents an in-depth analysis of patient rights protection, focusing on medical record confidentiality and the information disclosure system in Indonesian hospitals. The research utilizes a normative juridical approach, employing primary and secondary legal materials and combining statute and conceptual approaches. The analysis highlights gaps in the existing legal and policy frameworks that compromise patient rights, and the challenges healthcare providers face in maintaining medical record confidentiality and disclosure of information. These issues are further illuminated through a review of relevant academic literature, and corroborated by empirical evidence drawn from real-world case studies. Findings reveal a dichotomy between theoretical principles of patient rights and their practical implementation, accentuated by resource limitations, variations in law enforcement, and gaps in understanding among healthcare providers. The study concludes with recommendations for legal and policy reforms that can bridge these gaps, improve patient care, and strengthen trust in Indonesia's healthcare system. These reforms present both challenges and opportunities. While resource constraints and resistance to change may pose difficulties, the potential for improved patient care, enhanced public trust, and socio-economic development makes the pursuit of these reforms a necessary endeavour. This study contributes to a deeper understanding of patient rights protection and sets the stage for ongoing dialogue and action towards healthcare reform in Indonesia.